Wrath - Moalem, Sharon; Kraus, Daniel (Union Square and Co., 2022)
In a future much nearer than you think, where scientific experimentation is exploited for commercial profit, unwisely under-supervised cutting-edge technology creates a menace that threatens the very fabric of human existence. Sammy, a lab rat instilled with human genes and supersized intelligence, escapes into the world outside the lab where he, aware of humankind's cruelty in the name of science, has the potential to sire a rodent army capable of viciously overwhelming the human race.